EXPLORING THE LONG-TERM SHIFTS IN CONSUMER ENGAGEMENT WITH NON BANKING FINANCIAL SERVICES IN A HYBRID DIGITAL ECONOMY - ENACHESCU VLADIMIR-AURELIAN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This article examines the long-term changes in consumer engagement with non-banking financial services within the framework of a hybrid digital economy, focusing on the impacts of technological advancements, demographic shifts, and regulatory changes. The widespread adoption of digital financial services, accelerated by the COVID-19 pandemic, has significantly transformed consumer behavior, resulting in a marked increase in mobile payments, digital wallets, fintech solutions, and robo-advisory services. Utilizing publicly available data from national statistical institutes and Eurostat, we analyze trends in consumer preferences across various regions and demographics. Our findings indicate a distinct separation between early adopters, mainly younger and tech-savvy consumers, and older generations, who demonstrate slower rates of adoption. Furthermore, the research underscores the increasing significance of artificial intelligence, blockchain, and mobile banking in shaping the future of financial services. The paper also identifies regional disparities in digital finance adoption, with advanced economies showing higher levels of engagement compared to emerging markets. The study concludes with forecasts for the future of non banking financial services, emphasizing the continued expansion of fintech, the growing importance of AI and blockchain, and the evolution of regulatory frameworks. This article contributes to understanding the ongoing transformation in consumer engagement with financial services in the digital era, offering valuable insights for policymakers, financial institutions, and technology developers aiming to navigate the complexities of the hybrid digital economy.